The Genesis of accentuation in the behavior of the minor inclined to commit offences (Journal of actual problems of jurisprudence, 2019)
All accentuation considered temporary change in the nature, to smooth when growing up. At the same time, many of them go intomental illness, or stored for life. Accentuation are though extreme, but are normal. Therefore, the «accentuation of character» can notbe a psychiatric diagnosis.Keywords: genesis, accentuation, minors, offense, rule of law, character, pathology.